Athlete`s retention of a coach`s instruction before a judo competition - Mesquita, I.; Rosado, A.; Januario, N.; Barroja, E. (Journal of Sports Science & Medicine, 2008)
The aim of the present study was to analyze the instruction of the Judo coach immediately before the competition, in the process of preparation for the fights, looking to (1) study the coherency between the information which the coach transmits and that which the athlete retains; (2) identify the correlation between the coherency, the extension and the number of ideas conveyed by the coach; (3) determine if the retention varies in relation to variables such as the form and nature of the information, as well as the gender and practice category of the athletes. The participants were 11 coaches and 58 athletes of 3 categories: under- 15, under-17 and under-20, of both genders. One hundred and sixteen (116) instructional episodes were observed, which corresponds to four hundred and six (406) information units convoyed by the coaches. The coaches' instructions given before the competition were recorded in an audio and video register. After the coaches' instruction, the athletes were approached by the investigator and an interview was accomplished. To determine if the retention varies in relation to form and nature of the information and gender and practice category of the athletes, the non-parametric statistics, U de Mann-Whitney and Kruskal- Wallis, was used. Correlation of Spearman was applied to verify the degree of association between the coherency, the extension and the number of ideas conveyed by the coach.